Kemampuan Tanaman Kelapa Sawit Dalam Mereduksi Dust Fall Dari Perlintasan Transportasi Angkutan Batubara - Titik Fujianti; Junaidi Junaidi; Zulfikar Ali As (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2019)
Abstract: Abilities Of Oil Palm In Reducing Dusk Fall In (Trasnportation) Track Coal. In generally air environment changes because air pollution, activity in coal transportation give an air pollution impact is the dusk along coal transportation track. One of the ways to handling the dusk with planting barrier who can reducing the dusk particles. This research aimed to know palm oil abilities in reducing levels of submerged dusk. Method in this research is analytic observation, with cross sectional survey design. Population and sample of this research is measured dust level measured at 5 research location that is 1 m, 50 m, 100 m, 150 m, and 200 m. Width distance barrier in every location be measured 2 point of sample is without barrier and with barrier which to do in 5 replications. For data analysis, researchers used T-test independent, simple regression test and same subject anova test. The result of this research showed that the difference between levels of submerged dusk without barrier and with barrier. There is an effect distance to levels of the submerged dusk in length 1 m 173,66 ton/km2/month showed that reduction in length 200 m 17,06 ton/km2/month. Palm oil proved that reducing levels of submerged dusk in length 100 m levels of submerged dusk under environment standard.